Floristic inventory and ethnopharmacological insights of angiosperms in the Jokai Reserve Forest, Dibrugarh, North-East, India, with special reference to threat categorization of some species - Damini Dey; Kaushik Kumar Mech; Bikash Singh; Chetia, Pankaj (Ethnobotany Research and Applications, 2025)
Background: Jokai Reserve Forest, located only a few kilometers from the heart of Dibrugarh town in Assam, India, harbors a rich diversity of flora and fauna that remains largely unexplored in terms of floristic research. This study represents the first comprehensive attempt to compile a checklist of the flowering plants found in the reserve forest, with a particular focus on documenting the ethnomedicinal utilities allied with the therapeutic flora as practiced by the local communities residing around the forest. Methods: Surveys from June 2022 to May 2024 documented plants mainly collected during flowering/fruiting stages, with identification confirmed by taxonomy experts and regional floras. The data on the ethnobotanical utilities were gathered through structured field interviews with inhabitants. Results: A total of 353 angiosperms (270 dicots, 83 monocots) from 81 families and 273 genera were recorded. Herbs were most dominant (168 spp.), followed by trees (103) and shrubs (82). Most of the species found in this forest are not only valuable for the pharmaceutical biosphere but also found to be beneficial economically, especially as sources of timber, fuel wood, fruits, vegetables, ornamental plants, and as fodders. A total of 31 species fall under the Rare Endangered Threatened (RET) categories including 15 Critically Endangered (CR), 3 Endangered (EN), 3 Vulnerable (VU), and 11 Least Concern (LC) category. Conclusion: The present study is the first attempt to encounter, identify, and record the plant variety in Jokai Reserve Forest, making the initiative a significant scope to explore and comprehend the floral wealth and their potential ethnomedicinal properties. Keywords: Angiosperms, Checklist, Dibrugarh, Ethnomedicinal, Jokai, RET (Rare Endangered Threatened)